ANALYSIS OF STUDENTS' HOMEWORK MANAGEMENT LEVEL IN ISLAMIC RELIGIOUS EDUCATION SUBJECTS: A QUANTITATIVE DESCRIPTIVE STUDY - Ega Nasrudin; Wawan Hermawan; Fahmi Fazar; Edi Suresman; Agus Fakhruddin; Saepul Anwar; Roslan Ab Rahman (Program Studi PGSD Universitas Flores, 2025)
Homework is one way to improve students' learning achievements outside of extracurricular activities. Unfortunately, current phenomena show that homework is thought to have negative impacts such as academic fatigue or academic procrastination. This study aims to describe the quality of homework management for students in public high schools. The research approach uses a quantitative descriptive cross-sectional design. The data was shared in the form of a closed questionnaire and collected with a total sample of 646 students from a total population of 31,397 students. The location of this study was in one of the cities in Indonesia. The results of this study reveal that homework management is one aspect that needs attention in the Islamic Religious Education (IRE) subject. This aspect observes how well students manage their homework. The five main aspects include environment, time, motivation, emotion, and distraction. The results of the study found that the average level of student homework management is generally in the high category. In particular, the aspect that has the highest positive response in this study is the aspect of environmental management with an average indicator percentage of 92.80%. This aspect is followed by the aspects of emotion management (89.79%), motivation (87.70%), time (79.84%), and distraction (45.53%). This study shows that every aspect of homework management still needs improvement, especially the aspect of distraction. Based on the findings of this study, students tend to be easily distracted when doing their homework.